Faktor – Faktor Yang Mempengaruhi Stres Kerja Terhadap Keselamatan dan Kesehatan Kerja (K3) - Arini Salsabila Hasibuan; Muhammad Sahputra; Abdurrazaq Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
work stress is becoming an increasingly important issue in the workplace safety (K3) perspective. Factors that influence work stress have a significant impact on employee health and organizational productivity. This study aims to identify and analyze the factors that contribute to the level of work stress and its impact on K3. The research method used is a literature study that investigates various factors that can cause work stress, including excessive workload, role conflict, lack of control over work, lack of social support, job insecurity, and unsafe working conditions. In addition, the impact of work stress on K3 has also been analyzed, including an increased risk of work accidents, reduced attention span, and increased risk of physical and mental illness. Research shows that factors such as high job demands, lack of job control, and unsafe work environments contribute significantly to workplace stress levels. In addition, work stress also negatively affects K3, increasing the risk of accidents and occupational diseases. The practical implications of these findings are that organizations can influence workplace stress through intervention programs such as stress management training, encouraging work-life balance, increasing social support, and improving managed work conditions. Therefore, these initiatives not only improve K3 and employee well-being, but also help improve productivity and performance throughout the organization.